The pathology of joint replacement and tissue engineering. Issue 5 (May 2017) - Freemont, Anthony
Abstract: Joint replacement is very common and undertaken in most hospitals in one form or another. Tissue engineering of connective tissues generally, and joints in particular, is becoming more common. With increased usage, these techniques generate iatrogenic morbidity. The diagnosis and exclusion of iatrogenic disease is an increasingly important area of pathologists' working lives. This article discusses the disorders that can arise in association with joint replacement and tissue engineering of joints and describes a relatively new disease (Adverse Reaction to Metal Debris [ARMD]) the first of what may become many new disorders associated with the new therapeutics covered in this article.